7(x-5)=3(4-x)

Simple and best practice solution for 7(x-5)=3(4-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-5)=3(4-x) equation:


Simplifying
7(x + -5) = 3(4 + -1x)

Reorder the terms:
7(-5 + x) = 3(4 + -1x)
(-5 * 7 + x * 7) = 3(4 + -1x)
(-35 + 7x) = 3(4 + -1x)
-35 + 7x = (4 * 3 + -1x * 3)
-35 + 7x = (12 + -3x)

Solving
-35 + 7x = 12 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-35 + 7x + 3x = 12 + -3x + 3x

Combine like terms: 7x + 3x = 10x
-35 + 10x = 12 + -3x + 3x

Combine like terms: -3x + 3x = 0
-35 + 10x = 12 + 0
-35 + 10x = 12

Add '35' to each side of the equation.
-35 + 35 + 10x = 12 + 35

Combine like terms: -35 + 35 = 0
0 + 10x = 12 + 35
10x = 12 + 35

Combine like terms: 12 + 35 = 47
10x = 47

Divide each side by '10'.
x = 4.7

Simplifying
x = 4.7

See similar equations:

| 3+4=121 | | 26.5=n+2.08 | | x=11+6y | | 2LOG(X)-3LOG(X+7)= | | -3x-6(1+2x)=-111 | | 12x+30=3(4x-10) | | F(x)=-9x^2+7x+2 | | (3x^2-3xy^4)dx+(y^2-6x^2y^3)dy=0 | | 7y-6-2y+2=0 | | 2x+4(x+16)=130 | | 8m^2-11m+3=-5 | | 2r^2+3r-2+5r^2+8= | | (3x+9)(4x+7)= | | h(t)=-16t^2+60t+4 | | 2q+4-7+8q-q= | | 2x^2+11=-13 | | -2(v+3)+v=-30 | | -5p+32=12 | | 4g=692 | | 10t-12t=8 | | 3.5d+9.75=1+5.25d | | -2t+5=-7 | | a+34=57 | | -1(6x-2)=5(x+1) | | 4(10x+3)=-68 | | 3(c+7)-c= | | 4+8=-3 | | 6-x-x=17 | | 4a-3=9+a | | -19.4-15d+22d=44 | | cos(5x)+cos(5y)=0 | | 3(x-3)=2(6+x)1/2 |

Equations solver categories